1986
DOI: 10.1099/0022-1317-67-5-813
|View full text |Cite
|
Sign up to set email alerts
|

Some Highlights of Animal Virus Research in 1985

Abstract: For some time, the Editors of The Journal of General Virology have sought a format for presenting accounts of advances and notable events in virology, in a broader and more flexible manner than is afforded by the traditional review of a topic in depth. This article represents an experiment in such presentation. Its aim is to look at advances in virus research, and to present brief accounts of the most important and interesting work published within a calendar year. Subject to evaluation of the success of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1986
1986
1989
1989

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 86 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Our review of the highlights in virus research in 1988 differs from the previous highlight reviews ( McGeoch et al, 1986McGeoch et al, , 1987McGeoch et al, , 1988c in that it includes work on plant viruses as well as animal viruses. This change is an attempt to make these reviews more general and to indicate areas of similarity and contact between the viruses of different kingdoms.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Our review of the highlights in virus research in 1988 differs from the previous highlight reviews ( McGeoch et al, 1986McGeoch et al, , 1987McGeoch et al, , 1988c in that it includes work on plant viruses as well as animal viruses. This change is an attempt to make these reviews more general and to indicate areas of similarity and contact between the viruses of different kingdoms.…”
mentioning
confidence: 80%
“…The eight-stranded/~-barrel architecture was first observed with the structural proteins of small RNA viruses, and similar elements were subsequently reported for the adenovirus hexon protein (see reviews by McGeoch et al, 1986McGeoch et al, , 1987. Fuller & Argos (1987) reported that alphaviruses may also make use of this building block.…”
Section: Virus Structurementioning
confidence: 97%
“…
In 1986 we published a review article entitled 'Some highlights of animal virus research in 1985', in which we attempted to summarize important and interesting research on animal viruses published in 1985 (McGeoch et al, 1986b). The limitations of the exercise were recognized: coverage was selective rather than systematic and, outside clearly pre-eminent subjects, was overtly influenced by personal scientific interests.
…”
mentioning
confidence: 99%